Lipophilic analogues of D-cysteine prevent and reverse physical dependence to fentanyl in male rats - Bates, James N.; Getsy, Paulina M.; Coffee, Gregory A.; Baby, Santhosh M.; MacFarlane, Peter M.; Hsieh, Yee-Hsee; Knauss, Zackery T.; Bubier, Jason A.; Mueller, Devin; Lewis, Stephen J. (Frontiers in Pharmacology, 2024)
We examined whether co-injections of the cell-permeant D-cysteine analogues, D-cysteine ethyl ester (D-CYSee) and D-cysteine ethyl amide (D-CYSea), prevent acquisition of physical dependence induced by twice-daily injections of fentanyl, and reverse acquired dependence to these injections in freely-moving male Sprague Dawley rats. Injection of the opioid receptor antagonist, naloxone HCl (NLX, 1.5 mg/kg, IV), elicited a series of withdrawal phenomena that included cardiorespiratory and behavioral responses, and falls in body weight and body temperature, in rats that received 5 or 10 injections of fentanyl (125 μg/kg, IV), and the same number of vehicle co-injections. Regarding the development of physical dependence, the NLX-precipitated withdrawal phenomena were markedly reduced in fentanyl-injected rats that had received co-injections of D-CYSee (250 μmol/kg, IV) or D-CYSea (100 μmol/kg, IV), but not D-cysteine (250 μmol/kg, IV). Regarding reversal of established dependence to fentanyl, the NLX-precipitated withdrawal phenomena in rats that had received 10 injections of fentanyl (125 μg/kg, IV) was markedly reduced in rats that received co-injections of D-CYSee (250 μmol/kg, IV) or D-CYSea (100 μmol/kg, IV), but not D-cysteine (250 μmol/kg, IV), starting with injection 6 of fentanyl. This study provides evidence that co-injections of D-CYSee and D-CYSea prevent the acquisition of physical dependence, and reverse acquired dependence to fentanyl in male rats. The lack of effect of D-cysteine suggests that the enhanced cell-penetrability of D-CYSee and D-CYSea into cells, particularly within the brain, is key to their ability to interact with intracellular signaling events involved in acquisition to physical dependence to fentanyl.